Density and genetic relatedness increase dispersal distance in a subsocial organism. (7th January 2013) - Bitume, E. V.; Bonte, D.; Ronce, O.; Bach, F.; Flaven, E.; Olivieri, I.; Nieberding, C. M.
Abstract: Although dispersal distance plays a major role in determining whether organisms will reach new habitats, empirical data on the environmental factors that affect dispersal distance are lacking. Population density and kin competition are two factors theorised to increase dispersal distance. Using the two‐spotted spider mite as a model species, we altered these two environmental conditions and measured the mean dispersal distance of individuals, as well as other attributes of the dispersal kernel. We find that both density and relatedness in the release patch increase dispersal distance. Relatedness, but not density, changes the shape of the dispersal kernel towards a more skewed and leptokurtic shape including a longer 'fat‐tail'. This is the first experimental demonstration that kin competition can shape the whole distribution of dispersal distances in a population, and thus affect the geographical spread of dispersal phenotypes.